1985
DOI: 10.2307/3576590
|View full text |Cite
|
Sign up to set email alerts
|

Damage in DNA Irradiated with 1.2 MHz Ultrasound and Its Effect on Template Activity of DNA for RNA Synthesis

Abstract: When aqueous DNA solution was irradiated with 1.2 MHz continuous ultrasound in the presence of cysteamine, the number of ultrasound-induced double-strand breaks of DNA was not influenced, but the number of ultrasound-induced single-strand breaks of DNA was reduced to about one-fifth that of the irradiated control. When the effect of cysteamine on the template activity of the ultrasound-irradiated DNA was investigated, the cysteamine was found to exert a leveling effect on the linear decrease of the template ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Therefore, it is reasonable to assume that the mechanical effects of US cavitation, such as shear stress, are more essential for DSB formation in cells exposed to US. Consistent with this observation, our classical study in 1985 demonstrated that DSB induction in naked DNA is caused by the mechanical effects of US but not chemical effects [13]. However, from the available literature, there is no direct evidence showing a correlation between such mechanical effects and DSB formation in the cell nucleus.…”
Section: Us-induced Dsb Formation Mechanismsupporting
confidence: 65%
“…Therefore, it is reasonable to assume that the mechanical effects of US cavitation, such as shear stress, are more essential for DSB formation in cells exposed to US. Consistent with this observation, our classical study in 1985 demonstrated that DSB induction in naked DNA is caused by the mechanical effects of US but not chemical effects [13]. However, from the available literature, there is no direct evidence showing a correlation between such mechanical effects and DSB formation in the cell nucleus.…”
Section: Us-induced Dsb Formation Mechanismsupporting
confidence: 65%
“…Ultrasonic cavitation can produce many effects on a DNA molecule, including doublestrand breaks, single-strand breaks, rupture of hydrogen bonds, base destruction, and possibly cross-links. 50 These effects may be direct, due to the physical force placed on the molecule, or indirect, secondary to the production of highly reactive sonochemicals such as hydrogen peroxide. 48,50,52 Transfection assays therefore were performed in order to establish that the DNA in a sonicated liposome/DNA complex was still biologically functional.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Sonication has been demonstrated to cause DNA strand breaks. [50][51][52] We hypothesized that binding of plasmid DNA to cationic liposomes would protect it from damage due to sonication, and we determined that not only complex size but also resistance to DNA damage upon sonication was dependent on lipid composition. The results presented here suggest that DNA can be protected from damage due to ultrasonic cavitation when complexed to cationic liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…Biophysical modes of ultrasonic action can be classified into three main categories; thermal effect, direct effect and cavitation. It is generally accepted that many nonthermal effects of US in biologic systems are attributable to cavitation (Kondo et al 1985). Ultrasonic cavitation of aqueous media, which refers to the formation, growth and collapse of small gas bubbles, occurs over a wide range of frequencies and serves as mediator of any important effects of US (Riesz and Kondo 1992).…”
Section: Introductionmentioning
confidence: 99%